2014
DOI: 10.1038/ncomms4168
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species regulate the strength of inhibitory GABA-mediated synaptic transmission

Abstract: Neuronal communication imposes a heavy metabolic burden in maintaining ionic gradients essential for action potential firing and synaptic signaling. Although cellular metabolism is known to regulate excitatory neurotransmission, it is still unclear whether the brain’s energy supply affects inhibitory signaling. Here we show that mitochondrial-derived reactive oxygen species (mROS) regulate the strength of postsynaptic GABAA receptors at inhibitory synapses of cerebellar stellate cells. Inhibition is strengthen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 43 publications
7
63
0
Order By: Relevance
“…In our analyses, antioxidant enzymes such as superoxide dismutase 1 (SOD1), were found altered in hippocampal tissue (Focking et al, 2011b) ( Table 1 and 4) and were central to the top IPA protein networks in schizophrenia and bipolar disorder (Figures 1 and 2), supporting previous findings Coughlin et al, 2013;Emiliani et al, 2014). Increased brain levels of ROS lead to selective damage of fast-spiking GABAergic interneurons in rodent cortex (Behrens et al, 2007), and can directly regulate the strength of inhibitory GABAergic transmission at postsynaptic site through GABAA receptor recruitment (Accardi et al, 2014). Based on these findings, one can speculate that the effects of novel therapies for psychotic disorders involving anti-diabetic and antioxidant strategies (Dean et al, 2012;McIntyre et al, 2012;Reddy and Reddy, 2011) could partly be mediated via protection of hippocampal GABAergic interneuron function.…”
Section: Treated Animals Have Impairments In Hippocampal Long-term Pomentioning
confidence: 99%
“…In our analyses, antioxidant enzymes such as superoxide dismutase 1 (SOD1), were found altered in hippocampal tissue (Focking et al, 2011b) ( Table 1 and 4) and were central to the top IPA protein networks in schizophrenia and bipolar disorder (Figures 1 and 2), supporting previous findings Coughlin et al, 2013;Emiliani et al, 2014). Increased brain levels of ROS lead to selective damage of fast-spiking GABAergic interneurons in rodent cortex (Behrens et al, 2007), and can directly regulate the strength of inhibitory GABAergic transmission at postsynaptic site through GABAA receptor recruitment (Accardi et al, 2014). Based on these findings, one can speculate that the effects of novel therapies for psychotic disorders involving anti-diabetic and antioxidant strategies (Dean et al, 2012;McIntyre et al, 2012;Reddy and Reddy, 2011) could partly be mediated via protection of hippocampal GABAergic interneuron function.…”
Section: Treated Animals Have Impairments In Hippocampal Long-term Pomentioning
confidence: 99%
“…During synaptic transmission, the mitochondrial ATP generation produces ROS, which can regulate the strength of synaptic transmission. Specifically, it was shown that mitochondria-derived ROS selectively recruit α3 subunit-containing GABA A receptors to inhibitory synapses in order to increase the frequency and amplitude of inhibitory postsynaptic currents (IPSCs) in cerebellar stellate neurons (Accardi et al, 2014). Future studies are required to determine how mitochondrial dynamics impact on ROS-mediated regulation of synaptic transmission.…”
Section: Mitochondrial Transport and Bioenergeticsmentioning
confidence: 99%
“…However, this is an oversimplification of mitochondrial physiology. In addition to carrying out ATP synthesis through oxidative phosphorylation, mitochondria are also important for Ca 2+ signaling (Brini et al, 2014;Nicholls, 2005;Duchen, 2000;Clapham, 2007), cell death (Tait and Green, 2013;Duchen, 2000), steroid synthesis (Miller, 2011), reactive oxygen species (ROS) production and sequestration (Zorov et al, 2014;Hamanaka and Chandel, 2010;Shadel and Horvath, 2015;Accardi et al, 2014), and neurotransmitter synthesis and inactivation (Rowley et al, 2012;Bak et al, 2005;Waagepetersen et al, 2000). Given the importance of processes, such as ATP production, Ca 2+ transients, neurotransmitter metabolism and ROS signaling, in synaptic transmission it is not surprising that recent work has illustrated that perturbations in mitochondrial physiology exert profound effects on neuronal development and function.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work from our laboratory has revealed that mitochondrial-derived reactive oxygen species (mROS) strengthen inhibitory synapses of cerebellar stellate cells by a mechanism distinct in two important ways. First, synapse strengthening is mediated by the recruitment of ␣3-containing receptors and not resident ␣1-receptors (Accardi et al, 2014). Second, ␣3-receptors are targeted to functionally separate postsynaptic sites from ␣1-receptors (Accardi et al, 2014), implying that not all synapses are strengthened by mROS.…”
Section: Introductionmentioning
confidence: 99%
“…First, synapse strengthening is mediated by the recruitment of ␣3-containing receptors and not resident ␣1-receptors (Accardi et al, 2014). Second, ␣3-receptors are targeted to functionally separate postsynaptic sites from ␣1-receptors (Accardi et al, 2014), implying that not all synapses are strengthened by mROS. Whether this novel mechanism is unique to stellate cells or more commonly used throughout the CNS remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%